STUDENT'S ATTITUDE DESCRIPTION TOWARD PHYSICS ON SECONDARY SCHOOL - Maison Maison; Astalini Astalini; Dwi Agus Kurniawan; Senja Yuniyarsih (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2018)
DESKRIPSI SIKAP SISWA SMA NEGERI PADA MATA PELAJARAN FISIKA AbstractThe purpose of this study was to determine the attitudes of students toward the subjects of Physics at SMA Negeri 3 Muaro Jambi based on the attitude assessment indicators of TOSRA (Test of Science Related Attitudes). This research uses mixed methods research with an explanatory design. The research subjects were students of class X and XI MIA at SMA Negeri 3 Muaro Jambi totaling 160 students. Data analysis techniques used descriptive statistics for quantitative data and Miles Huberman analysis for qualitative data. The results of the research on the three indicators show that students are categorized as having a right attitude on the indicator 'social implications on physics' with a percentage of 52%, sufficient attitude on the indicator 'normality of scientists' with a percentage of 63%, and enough attitude on the dimension of 'career interest in physics' with 58% percentage. A high rate of these three categories is supported by qualitative data from interviews which state that physics discoveries have significant benefits for technological development, the work of scientists requires a lot of time in the laboratory, and students have the desire to work in the field of physics, but feel they cannot master physics concepts.AbstrakTujuan penelitian ini adalah untuk mengetahui sikap siswa terhadap mata pelajaran Fisika di SMA Negeri 3 Muaro Jambi berdasarkan indikator penilaian sikap dari TOSRA (Test of Science Related Attitudes). Penelitian ini menggunakan metode penelitian campuran (mixed methods research) dengan desain explanatory. Subjek penelitian adalah siswa kelas X dan XI MIA di SMA Negeri 3 Muaro Jambi yang berjumlah 160 siswa. Teknik analisis data menggunakan statistik deskriptif untuk data kuantitatif dan analisis Miles Huberman untuk data kualitatif. Hasil penelitian pada ketiga indikator menunjukkan bahwa siswa dikategorikan memiliki sikap baik pada indikator ‘implikasi sosial terhadap fisika’ dengan presentase 52%, sikap cukup pada indikator ‘normalitas ilmuwan’ dengan persentase 63%, dan sikap cukup pada dimensi ‘ketertarikan berkarir dibidang fisika’ dengan persentase 58%. Persentase yang tinggi ketiga kategori ini didukung oleh data kualitatif hasil wawancara yang menyatakan bahwa penemuan-penemuan fisika memiliki manfaat yang besar untuk perkembangan teknologi, pekerjaan ilmuwan memerlukan waktu yang banyak di laboratorium, dan siswa memiliki keinginan untuk bekerja di bidang fisika, tetapi merasa tidak memiliki kemampuan dalam menguasai konsep-konsep fisika.